Ventilation with end-expiratory pressure in acute lung disease - Falke, Konrad J. (1972)
In 10 patients with severe, acute respiratory failure we studied the effects of positive end-expiratory pressure when intermittent positive pressure ventilation (IPPV) with inspired oxygen (F(I(O(2)))) up to 0.5 failed to maintain arterial oxygen tension (P(a(O(2)))) above 70 torr. Positive end-expiratory pressures (PEEP) of 0, 5, 10, and 15 cm H(2)O were applied for 30-min periods each and in random order. Blood gas exchange, lung volumes, compliance, and hemodynamics were studied at each level of PEEP. P(a(O(2))) (F(I(O(2))) = 1.0) rose linearly with elevation of PEEP, the mean increase being from 152 to 347 torr, or 13 torr/cm H(2)O PEEP. Mean functional residual capacity (FRC) was 1.48±0.78 liters at zero PEEP (i.e., IPPV) and the increase was essentially linear, reaching 2.37 liters at 15 cm H(2)O PEEP. P(a(O(2))) and FRC showed a close correlation. Total and lung static compliance were greater during ventilation with high than with low levels of PEEP. The increase in P(a(O(2))) correlated with the specific lung compliance. Dynamic lung compliance decreased progressively with rising levels of PEEP except for an increase with 5 and 10 cm H(2)O PEEP in patients with initial values of 0.06 liter/cm H(2)O or higher. Cardiac index fell in some patients and rose in others and there was no correlation of mean cardiac index, systemic blood pressure, or peripheral vascular resistance with level of PEEP. The most probable explanation for the effect of PEEP on P(a(O(2))) and compliance is recruitment of gas exchange airspaces and prevention of terminal airway closure.